Physical characteristics and somatotype of soccer players according to playing level and position - Hazir, T. (Journal of Human Kinetics, 2010)
The purpose of this study was to assess the physical characteristics of soccer players according to playing level and position. A total of 305 professional male soccer players [Turkish Super League (SL) (n = 161) and Turkish First League (FL) (n = 144)] were involved in this study. All data were gathered at the beginning of preparatory period of mid-eason. Height, weight, flexed and tensed upper arm and calf girths, humerus and femur biepicondylar breadths, and four skinfold thicknesses ( triceps, subscapular, supraspinale, and medial calf) were measured. Somatotypes were estimated using the Heath-Carter method. SL players were older (p.0.002), and heavier (p.0.007) than FL players, while height (p . 0.497) was similar between SL and FL groups. There were significant differences for BW (p.0.000), and height (p.0.000) between playing positions. Goalkeepers were taller (p.0.000), and heavier (p.0.001) than other players. Midfielders were shorter (p.0.013) than other players, however, they were lighter than forwards (p.0.008). The mean somatotype of the overall players was 2.4-4.8-2.3 (0.9-0.8-0.7) in SL and was 3.0-4.5-2.6 (0.9-0.9-0.8) in FL. SL players were more mesomorphic (p.0.01), less endomorphic (p.0.000), and less ectomorphic (p.0.001) than FL players. Except for goalkeepers, there were significant differences in paired means between whole somatotype means of the SL and FL according to playing positions. The results of the present study demonstrate that both physical characteristics and somatotype of players were significantly different between playing levels and positions. Although the somatotype of soccer players in both levels was dominated by the mesomorph category, players at the higher playing level were more mesomorphic, and less endomorphic and ectomorphic than players at the lower level at all playing positions.